Signal Detection of Potentially Drug-Induced Liver Injury in Children Using Electronic Health Records - Yu, Yuncui; Nie, Xiaolu; Song, Ziyang; Xie, Yuefeng; Zhang, Xuan; Du, Zhaoyang; Wei, Ran; Fan, Duanfang; Liu, Yiwei; Zhao, Qiuye; Peng, Xiaoxia; Jia, Lulu; et al. (Frontiers in Pediatrics, 2020)
Background: This study proposes a quantitative 2-stage procedure to detect potential drug-induced liver injury (DILI) signals in pediatric inpatients using an electronic health records (EHRs) database. Methods: Eight years of medical data from a constructed database were used. A two-stage procedure was adopted: (i) stage 1: the drugs suspected of inducing DILI were selected and (ii) stage 2: the associations between the drugs and DILI were identified in a retrospective cohort study. Results: A total of 1196 drugs were initially selected, of which 12 drugs were potentially identified as being associated with DILI. Eleven drugs (fluconazole, omeprazole, sulfamethoxazole, vancomycin, granulocyte colony-stimulating factor (G-CSF), acetaminophen, nifedipine, fusidine, oseltamivir, nystatin and meropenem) were found to be associated with DILI. Of these, two drugs, nystatin (OR=1.39, 95%CI:1.10-1.75) and G-CSF (OR=1.91, 95%CI:1.55-2.35), were considered new potential signals in both adults and children. Three drugs (nifedipine (OR=1.77, 95%CI:1.26-2.46), fusidine (OR=1.43, 95%CI:1.08-1.86) and oseltamivir (OR=1.64, 95%CI:1.23-2.18) were considered new signals in children. The other drugs associated with DILI had been confirmed in previous studies. Conclusions: A quantitative algorithm to detect potential signals of DILI has been described. Our work contributes to the utilization of EHR data for pharmacovigilance and provides candidate drugs for further causality assessment studies.